The EFFECT OF POLYSTYRENE PAPER STYROFOAM FEED ON SURVIVORSHIP AND GROWTH OF Tenebrio molitor L. - Subchan, Wachju; Musyarofah, Alivinda; Susilo, Vendi (SEAMEO BIOTROP, 2024)
Polystyrene Paper Styrofoam (PSP) styrofoam waste is one of the plastic waste that is difficult to degrade. However, from the recently research reported that the PSP styrofoam can be degradated by Tenebrio molitor L. The degradation depends on composition of PSP styrofoam as a part of feeding. This research was aimed to get the composition of good feed to increase the degradation rate of the PSP styrofoam waste, but it still had a good effect on the survivorship and growth of T molitor L. larvae. This research was an experimental laboratory and designed using a control and seven treatments with 3 replications. The parameters observed were survivorship, growth in body length, biomass, and waste degradation rate. The data obtained was analysed using Anova and Duncan test. The results showed that differences in PSP styrofoam waste feed had a significant effect on survivorship (p=0.00), on the growth of body length (p=0.002) and biomass (p=0.00), and waste degradation rate (p=0.02). The research revealed that lower the composition of PSP styrofoam and higher the composition of concentrate combination effected on increasing the survivorship, growth, and waste degradation rate. The result shows that 1 kg T molitor L. larvae can degrade 0.25 kg of PSP styrofoam waste for 60 days. The finding can be used to solve the problem according to the styrofoam pollution.